PEMBUATAN ALAT PENJERNIH AIR UNTUK MENINGKATKAN KUALITAS AIR SUMUR GALI BERGAMBUT - Gulo, Ernima; Wondong, Gaudensia Rika; Iswadi, Didik (Ensiklopedia of Journal, 2024)
Abstract : Water is an essential chemical compound for humans and other living creatures. For urban people, finding water is difficult because of extreme droughts, while for rural people, water has to be sought deep in the woods. The aim of this research is to find a water purifier that uses a cheap and environmentally friendly filter medium. It is also made of red and acidic water that can be used as a daily routine. In this study, the design of a water purification device consisted of three different designs with silica sand, chill, activated carbon, grass, and fine fabric filter components (different arrangements for each design), then performed the water analysis of the design results of the device, and compared water availability. The results of the research showed that the best design is the third design where the test results in the laboratory showed the best results with a hardness value of 1.76 NTU, TDS 137 Mg/L, total alkalinity of 120 Mg / L, nitrite 0.Keywords: Instrument design, water, rottenness, TDS, pH